2022
DOI: 10.30773/pi.2021.0365
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Depression and Anxiety in Korean Adolescents During the COVID-19 Pandemic

Abstract: Objective This study was performed to identify factors associated with depression and anxiety among Korean adolescents during the coronavirus disease (COVID-19) pandemic.Methods We conducted a cross-sectional study of 1,898 Korean adolescents (55.2% male, 44.8% female) ranging in age from 12 to 17 years (mean±standard deviaion age, 15.4±2.6 years). Depression and anxiety were defined as a Patient Health Questionnaire-9 score ≥10 and Generalized Anxiety Disorder-7 score ≥10, respectively. Other questionnaires i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 94 publications
2
5
0
Order By: Relevance
“…In terms of gender differences, female respondents expressed more concerns, which is consistent with the results of many other studies [ 21 , 22 , 24 , 32 , 36 , 38 ]. Girls were more concerned about the difficulty of returning to normal life and were more likely to express a desire to return to pre-pandemic life.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In terms of gender differences, female respondents expressed more concerns, which is consistent with the results of many other studies [ 21 , 22 , 24 , 32 , 36 , 38 ]. Girls were more concerned about the difficulty of returning to normal life and were more likely to express a desire to return to pre-pandemic life.…”
Section: Discussionsupporting
confidence: 91%
“…The fear of contracting the virus, as well as the fear of infecting loved ones, was frequently addressed by children and adolescents surveyed during the pandemic [ 19 , 20 , 21 , 22 , 23 , 24 ]. Sarkadi et al [ 17 ] found that 60% of the children and adolescents surveyed in Sweden worried that they or their relatives would contract the virus or die as a result.…”
Section: Introductionmentioning
confidence: 99%
“…After deduplication, we assessed 24,926 abstracts for eligibility (see Figure 1). After the screening process, 191 studies were included in the systematic review 50,51,56–244 with a total...…”
Section: Resultsmentioning
confidence: 99%
“…Gratitude has shown a positive effect on individuals who have experienced severe trauma [ 28 ], and gratitude training reduces physical symptoms and negative emotions and promotes bonding in interpersonal relationships [ 29 ]. Gratitude has also been shown to act as a protective factor against psychological stress and depression during the COVID-19 pandemic [ 30 - 32 ]. In addition, participating in gratitude training has been reported to lower the level of anxiety significantly [ 33 ], suggesting the possibility of controlling the relationship between the fear of COVID-19 infection and anxiety.…”
Section: Introductionmentioning
confidence: 99%